Distribution characteristics of stress on the vertebrae following different ranges of excision during Modified Anterior Cervical Discectomy and Fusion: A correlation study based on finite element analysis - Jing-Lai Xue; Liang Chen; Xuan-Yun Qiu; Xiong-Han Lian; Jing Lu; Zhong Liao; Jing-Yuan Yang; Huo-Huo Xue (BMC Musculoskeletal Disorders, 2024)
Abstract Background Modified Anterior Cervical Discectomy and Fusion with specific resection ranges is an effective surgical method for the treatment of focal ossification of the posterior longitudinal ligament (OPLL). Herein, we compare and analyse the static stress area distribution by performing different cuts on an original ideal finite element model. Method A total of 96 groups of finite element models of the C4–C6 cervical spine with different vertebral segmentation ranges (width: 1–12 mm, height: 1–8 mm) were established. The same pressure direction and size were applied to observe the size and distribution area of stress following various ranges of excision of the C5 vertebral body. Results Different cutting areas had similar stress aggregation points. As the contact area decreased, the stress and the bearing above area increased. The correlation of stress area variation was highest between the 1–2 MPa and 6 MPa–Max regions (Rho = − 0.975). In the surface visualisation model fitting, the width and height were of different ratios in different stress regions. The model with the best fitting degree was the 1–2 MPa group, and the equation fitting (Rho = 0.966) was as follows: Area = 908.80 − 25.92 × Width + 2.71 × Height. Conclusion Modified Anterior Cervical Discectomy and Fusion with different resection ranges exhibited different stress areas. In a specific resection range of the cervical spine (1–12 mm, 0–8 mm), area conversion occurred at a threshold of 4 MPa. Additionally, the stress was concentrated at the contact points between the vertebral body and the rigid fixator.